AB0519 Auto-antibody titers for monitoring rituximab therapy in rheumatoid arthritis. (23rd January 2014) - Vizioli, C.R.; Viana, V.; Ribeiro, A.C.; Saad, C.; Moraes, J.; Bonfa, E.; Calich, A.L.
Abstract : Background: Monitoring auto-antibody titers has been suggested as a means of assessing treatment efficacy in rheumatoid arthritis (RA) patients. Several studies evaluated the effect of anti-TNF antagonist treatment on auto-antibody titers like rheumatoid factor, anti-cyclic citrullinated peptide (anti-CCP) and anti-mutated citrullinated vimentin (anti-MCV) 1 . There are however few studies that evaluated the correlation between antibodies titers and RA clinical activity levels in rituximab therapy and no data regarding the use of anti-MCV antibody 2 . Objectives: The aim of this study was to evaluate the correlation between titers of rheumatoid factor, anti-CCP, anti-MCV antibodies and RA clinical activity before and after rituximab therapy. Methods: Forty-one patients who underwent treatment with rituximab were consecutively selected for this study. Data were obtained in an ongoing electronic database protocol carried out for all patients at 1-4 months intervals which consists of an extensive clinical and laboratory evaluation, including clinical response by DAS 28, morning stiffness duration, physician's global assessment and HAQ (Health Assessment Questionnaire). Anti-MCV, anti-CCP and RF levels were determined by ELISA, before and after four months of treatment. Pre- and post-treatment comparisons were performed using Wilcoxon or Student t -paired tests and Pearson correlation coefficient. Results: 95% of the patients were female with a mean age of 54±10 years and mean disease duration of 17±9 years. A significant decrease in DAS 28 (5.6 vs. 4.1, p<0.001), morning stiffness (65 vs. 17 min, p<0.001), RF (283 vs. 160, p<0.001) and anti-MCV (507 vs. 363, p<0.001) was observed after rituximab treatment whereas no difference was detected for anti-CCP antibodies (160 vs. 150 p=0.07). Of note, after four months a significant reduction in IgG levels (1302 vs. 1136, p<0.001) and IgM levels (176 vs. 128, p<0.001) was observed in these patients. However, DAS 28 reduction was not correlated neither with RF (0.031, p=0.848), anti-CCP (0.254, p=0.11) and anti-MCV (-0.116, p=0.47). Likewise, all other clinical parameters did not correlate with antibodies levels (p>0, 05). Conclusions: We demonstrated that auto-antibody titers decreases in RA patients under rituximab treatment, partially explained by the drug induced reduction in immunoglobulin levels. The lack of correlation with DAS 28 response precludes its use for monitoring rituximab therapy. References: Nicaise Roland P, Grootenboer Mignot S, Bruns A, Hurtado M, Palazzo E, Hayem G, Dieudé P, Meyer O, Chollet Martin S. Antibodies to mutated citrullinated vimentin for diagnosing rheumatoid arthritis in anti-CCP-negative patients and for monitoring infliximab therapy. Arthritis Res Ther. 2008;10(6):R142. Cambridge G, Leandro Mj, Edwards JC, Ehrenstein MR, Salden M, Bodman-Smith M, Webster AD. Serologic Changes Following B Lymphocyte Depletion Therapy for Rheumatoid Arthritis. Arthritis Rheum. 2003 Aug;48(8):2146-54. Disclosure of Interest: None Declared